Comparison of separated and combined photodegradation and biofiltration technology for the treatment of volatile organic compounds: A critical review. Issue 8 (15th February 2022) - Han, Meng-Fei; Hu, Xu-Rui; Wang, Yong-Chao; Tong, Zhen; Wang, Can; Cheng, Zhuo-Wei; Feng, Ke; Qu, Miao-Miao; Chen, Jian-Meng; Deng, Ji-Guang; Hsi, Hsing-Cheng
Abstract: The continuous emissions of volatile organic compounds (VOCs) from the industrial process cause serious environmental problems and pose a threat to human health. Photodegradation technology and biofiltration technology are efficient to control VOCs emissions. Recently, the researches on combined photodegradation and biofiltration technology have been attractive, since it could overcome the challenges in the application of the separated technologies, such as toxic by-product emission, excess biomass accumulation, and shock loading. However, no review has published to report the development of the combined technology comprehensively. In this paper, the challenges of the separated photodegradation and biofiltration technology in treating VOCs are documented firstly. Then, the advantages of the combined technology are illustrated by comparing with the separated photodegradation and biofiltration technology, respectively. Finally, the interaction mechanisms between photodegradation and biofiltration are also discussed. The advantages of the combined technology could promote its application in practical engineering. Graphical Abstract: UF0001